Dark quarkonium formation in the early universe - Geller, M.; Iwamoto, S.; Lee, G.; Shadmi, Y.; Telem, O. (The journal of high energy physics, 2018)
A bstract The relic abundance of heavy stable particles charged under a confining gauge group can be depleted by a second stage of annihilations near the deconfinement temperature. This proceeds via the formation of quarkonia-like states, in which the heavy pair subsequently annihilates. The size of the quarkonium formation cross section was the subject of some debate. We estimate this cross section in a simple toy model. The dominant process can be viewed as a rearrangement of the heavy and light quarks, leading to a geometric cross section of hadronic size. In contrast, processes in which only the heavy constituents are involved lead to mass-suppressed cross sections. These results apply to any scenario with bound states of sizes much larger than their inverse mass, such as U(1) models with charged particles of different masses, and can be used to construct ultra-heavy dark-matter models with masses above the naïve unitarity bound. They are also relevant for the cosmology of any stable colored relic.